2009
DOI: 10.3184/030823409x431328
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of Phenolic Hydroxyl Group and Demethylation of Anisoles

Abstract: A mild methylation of phenolic hydroxyl groups with iodomethane was enabled in the presence of sodium bis(trimethylsilyl)amide at room temperature. The reverse reaction, namely demethylation of methyl phenyl ethers, was easily achieved by microwave heating with neat iodotrimethylsilane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…To improve the efficiency of the demethylation of 10, a further screen of the reaction parameters was carried out. Based on the literature, several different methods, including the use of LiCl, 15 LiI, 16 TMSI 17,18 (TMS = trimethylsilyl), BCl 3 , 19 the ionic liquid (Me 3 NH) + (Al 2 Cl 7 ) -, 20 BBr 3 /catechol, 21 AlCl 3 , 22 and AlCl 3 /EtSH 23 were briefly examined. The results showed that while other methods gave complex mixtures with low yields, the combination of AlCl 3 (5.0 equiv) and EtSH (5.0 equiv) in DCM at 0 °C afforded 6 in 76% isolated yield.…”
mentioning
confidence: 99%
“…To improve the efficiency of the demethylation of 10, a further screen of the reaction parameters was carried out. Based on the literature, several different methods, including the use of LiCl, 15 LiI, 16 TMSI 17,18 (TMS = trimethylsilyl), BCl 3 , 19 the ionic liquid (Me 3 NH) + (Al 2 Cl 7 ) -, 20 BBr 3 /catechol, 21 AlCl 3 , 22 and AlCl 3 /EtSH 23 were briefly examined. The results showed that while other methods gave complex mixtures with low yields, the combination of AlCl 3 (5.0 equiv) and EtSH (5.0 equiv) in DCM at 0 °C afforded 6 in 76% isolated yield.…”
mentioning
confidence: 99%